2006
DOI: 10.1021/jp0634398
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Effect of the Preparation Technique on the State of Cobalt Ions in BEA Zeolites Evidenced by FTIR Spectroscopy of Adsorbed CO and NO, TPR and XRD

Abstract: The state of cobalt in two BEA zeolites was studied by XRD, TPR, and FTIR spectroscopy using CO and NO as probe molecules. One of the samples, CoAlBEA (0.4 wt % of Co), was prepared by conventional ion exchange and the other, CoSiBEA (0.7 wt % Co), by a two-step postsynthesis method involving dealuminated SiBEA zeolite. The introduction of Co into SiBEA leads to an increase of unit cell parameters of the BEA structure and to the consumption of silanol groups in vacant T-sites of the dealuminated zeolite. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 44 publications
7
53
1
Order By: Relevance
“…The crystalline structure was preserved during the acid treatments, which is in agreement with the literature for HNO 3 -treated beta materials [83,[85][86][87][88][89]. The SSIE process did not lead to measurable changes in the crystalline structure of the materials deAl-betan.…”
Section: Characterisation Of the Modified Zeolite Beta Materialssupporting
confidence: 90%
“…The crystalline structure was preserved during the acid treatments, which is in agreement with the literature for HNO 3 -treated beta materials [83,[85][86][87][88][89]. The SSIE process did not lead to measurable changes in the crystalline structure of the materials deAl-betan.…”
Section: Characterisation Of the Modified Zeolite Beta Materialssupporting
confidence: 90%
“…According to the literature [21][22][23][24], the band at 3744 cm -1 corresponds to external silanols, and that at 3737 cm -1 , to internal silanols. The broad feature at 3530 cm -1 corresponds to hydrogen-bonded SiOH groups located in hydroxyl nests or framework-defect sites [23].…”
Section: Background Ir Spectramentioning
confidence: 91%
“…The broad feature at 3530 cm -1 corresponds to hydrogen-bonded SiOH groups located in hydroxyl nests or framework-defect sites [23]. The band at 3608 cm -1 arises from the zeolite acidic Al-O(H)-Si hydroxyls [21][22][23][24]. Finally, the 3663 cm -1 band corresponds to Al-OH groups [21][22][23][24].…”
Section: Background Ir Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that C-O frequency decreases as the positive charge of cations increases due to stronger p-back donation of d-electrons from cations to CO p* antibonding orbitals. Hadjiivanow et al [18][19][20] reported the presence of a set of bands in the 2040-2140 cm -1 range assigned to carbonyl species of Co ? in reduced CoZSM-5.…”
Section: Reduction By Nomentioning
confidence: 99%